PEMAHAMAN MASYARAKAT KECAMATAN MERGANGSAN, GONDOKUSUMAN, UMBULHARJO DAN KOTAGEDE YOGYAKARTA TERKAIT ANTIBIOTIKA Studi Pendahuluan Dalam Pengembangan Materi dan Metode Edukasi Dengan Pendekatan Secara Kualitatif: Diskusi Kelompok Terarah (DKT) - Titien Siwi Hartayu; Yosef Wijoyo; Lucia Wiwid Wijayanti (Sanata Dharma University, 2013)
Abstract: Antibiotics will be used safely when it is used rationally, and rational use of antibioticsneed an appropriately of knowledge. In accordance to achieve appropriately knowledge aboutantibiotics, it is important to identify the level of knowledge about antibiotics to improve aneducational method and material about antibiotics. As a qualitative study using focus groupdiscussion (FGD) among residence of Four Sub-district in Yogyakarta City, e.g.: Mergangsan,Gondokusuman, Umbulhardjo and Kotagede. There was eight key person of each sub districtinvolved in the study. The inclusion criteria are: Residence of one of the four sub-districts withage above 17 years old, willing to attend the activities. The exclusion criteria are: residence withPharmacy education background, moving limited and mental disability. Results of the studyshow the characteristic demography of the participants are: 5 Female and 3 Male, age rangefrom 40 to 52 years old, with educational level: 5 participants are high school graduated and 3participants are University graduated. All of participants are key person of each sub districtwhose familiar with the residences and the environmental where they are living. All ofparticipants mention that they do not know about antibiotics et all including resistance and otherrisks of irrational use of antibiotics. All of participants asking for complete information aboutantibiotics which simple, accessible and could be socialized through the routine activities inevery sub district e.g.: PKK (mothers gathering). In conclusion, the level of participants'knowledge about antibiotics is still low, and need to be improved. Complete information aboutantibiotics in a simple form has to be developed as an educational material.Keywords: Focus Group Discussion, Antibiotics, Knowledge